Interpersonal Mattering and Students’ Friendship Quality as Predictors of Subjective Wellbeing - Kylie Kai Ni Yap; Kususanto Ditto Prihadi; Susanna Lin Hong Poay; Fahyuni Baharuddin (International Journal of Public Health Science (IJPHS), 2022)
This non-experimental correlational study aimed to investigate whether interpersonal mattering would be a better predictor of subjective wellbeing than friendship quality. 119 emerging adults drawn from the public responded to the Google Form posted on social media. Participants were asked to fill up the McGill Friendship Questionnaire-Friend’s Functions (MFQFF), Mattering to Others Questionnaire (MTOQ), and Subjective Happiness Scale (SHS). The study hypothesized that friendship quality would predict subjective wellbeing (H1), interpersonal mattering would predict subjective wellbeing (H2) and interpersonal mattering would be a better predictor of subjective wellbeing than friendship quality (H3). Results showed that H2 and H3 were supported but H1 was not supported. Therefore, when people increased their sense of mattering, it may be likely to increase their subjective wellbeing.